Polymyositis-Dermatomyositis and Interstitial Lung Disease in Pregnant Woman Successfully Treated with Cyclosporine and Tapered Steroid Therapy - Saito Mayu; Sakiko Isojima; Yoko Miura; Shinichiro Nishimi; Mika Hatano; Takahiro Tokunaga; Ryo Takahashi; Keiko Koide; Yusuke Miwa (Case Reports in Rheumatology)
Polymyositis-dermatomyositis is extremely rare during pregnancy, and immunosuppressive therapy should be administered after carefully considering the effects on both the mother and fetus. Several reports have associated the disease activity with fetal prognosis, higher rates of eclampsia, preterm births, and fetal deaths. We report our experience with a patient who was diagnosed with polymyositis-dermatomyositis complicated by interstitial lung disease during pregnancy and was treated with a combination-immunosuppressant regimen. To the best of our knowledge, this is the first case wherein cyclosporine was used concomitantly with a steroid for the treatment of polymyositis diagnosed during pregnancy, with successful outcome of childbirth without any complications.